2008
DOI: 10.1152/ajpcell.00063.2008
|View full text |Cite
|
Sign up to set email alerts
|

Effect of temperature on cross-bridge properties in intact frog muscle fibers

Abstract: It is well known that the force developed by skeletal muscles increases with temperature. Despite the work done on this subject, the mechanism of force potentiation is still debated. Most of the published papers suggest that force enhancement is due to the increase of the individual cross-bridge force. However, reports on skinned fibers and single-molecule experiments suggest that cross-bridge force is temperature independent. The effects of temperature on cross-bridge properties in intact frog fibers were inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
20
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 22 publications
8
20
0
Order By: Relevance
“…Moreover, a temperature-induced enhancement of actomyosin activity is consistent with previous observations that temperature increases contractility in fibroblasts [46] and activates the actomyosin machinery [4752]. Such an increase has been attributed either to an enhancement of the mean force developed by the individual actomyosin cross bridges [5052] or to a change in the cross-bridge number [47, 49]. The parallel behaviour of G ′ and P observed here indicates that the link between both magnitudes is maintained at different temperatures.…”
Section: Discussionsupporting
confidence: 90%
“…Moreover, a temperature-induced enhancement of actomyosin activity is consistent with previous observations that temperature increases contractility in fibroblasts [46] and activates the actomyosin machinery [4752]. Such an increase has been attributed either to an enhancement of the mean force developed by the individual actomyosin cross bridges [5052] or to a change in the cross-bridge number [47, 49]. The parallel behaviour of G ′ and P observed here indicates that the link between both magnitudes is maintained at different temperatures.…”
Section: Discussionsupporting
confidence: 90%
“…The recovery of tension during phase 2 was much faster at 35 than at 24°C. We also found that temperature increase from 24 to 35°C did not affect fiber stiffness, indicating that tetanic force potentiation by temperature, in this range, is mainly due to the increase of the average force per crossbridge in agreement with our previous findings [19,20]. …”
Section: Discussionsupporting
confidence: 93%
“…Measurements on the same group of fibers showed that fiber stiffness at tetanus plateau did not increase significantly from 24 to 35°C, indicating that force potentiation by temperature occurred without changes in attached crossbridge number (proportional to stiffness) consistently with the idea that temperature increases the individual crossbridge force as suggested previously [19,20]. We also measured the ratio ( dl/l f )/( dp / P 0 ), defined as y 0f , which corresponds to the relative extension (% of l f ) at the tetanus plateau, of all the elastic components of the fibers: tendon, myofilament and crossbridges.…”
Section: Resultssupporting
confidence: 79%
“…When activated muscle fibers and myofibrils are stretched at low speeds [Յ2 optimal length (L o )/s], cross bridges have to resist the opposing forces while attached to actin, which causes the force to increase in two phases: 1) a fast increase that happens over the extension of a few nanometers and subsequently 2) a slow increase or a stabilization of force (16,23,39,41,43). Rapid stretches (Ͼ10 L o /s) produce a break in the force rise also associated with the mechanical detachment of cross bridges and corresponding well to the transition in force observed during slower stretches (2,12,13). The detachment happens after the cross bridges reach a critical extension length (L c ), commonly observed in lengths between 8 and 20 nm/halfsarcomere (HS), depending on the experimental condition (16,23,39,43).…”
mentioning
confidence: 78%